Aerobic Oxidation of Methyl‐substituted β‐Carbolines Catalyzed by N‐Hydroxyphthalimide and Metal Catalyst. Issue 43 (23rd November 2018) - Qiu, Hongda; Liang, Weida; Zhang, Gongjun; Lin, Miaoman; Liu, Wanmin; Gao, Zhanghua; Wei, Wenting; Tang, Chunlan; Jin, Haixiao; Liang, Hongze; Yan, Xiaojun
Abstract: Carboxylic functionalized β ‐carbolines were successfully synthesized in good to excellent yields and high selectivity under mild conditions by aerobic oxidation in the presence of NHPI and transition metal salt using molecular oxygen as an oxidizing agent. A variety of derivatives of fascaplysin thus are available for structure‐bioactivity investigations. Abstract : Carboxylic functionalized β ‐carbolines have been synthesized in good to excellent yields and high selectivity by oxygen in the presence of NHPI and transition metal salt under mild conditions